The 70-year history of metallurgical production at the Minsk automobile plant and prospects of its development - P. S. Gurchenko; Yu. E. Cazyuchits; A. M. Skibar; B. A. Chepyzhov (Литьë и металлургия)
The data on the creation of the Minsk automobile plant, the formation and development of its foundre shops, measures taken to ensure the growth of the volume and quality of iron and steel casting on MAW are given. The measures to improve working conditions at the plant and improve the environmental situation are shown. The brief characteristics of the technological processes created at MAW for obtaining steel cast heat-treated shot and briquetting metal chips using induction heating, as well as modern molding and core mixtures and equipment developed at MAW and eqiopment created at OJSC «BELNIILIT», are given.